Twin heart with a fused atria and separate ventricles in conjoined twins - Ambar Sameer; Halkati Prabhu; Patted Suresh; Yavagal S (Wolters Kluwer Medknow Publications, 2010)
One of the most interesting congenital malformations is that of conjoined twins. We report echocardiographic features of twin heart in dicephalus, tribrachius, dispinous, thoracoomphalopagus twin. It showed two hearts fused at atrial level. Right-sided heart had single atrial chamber with a single ventricle. A single great vessel, aorta, originated from it. Left-sided heart was well developed with two atria and two ventricles. There was a small mid muscular ventricular septal defect and a small patent ductus arteriosus. Great arteries had normal origins.